Profile of Post-Certification Public High School Teachers' Teaching Behavior - Wedasuwari, Ida Ayu Made; Suciari, Ni Komang Dina; Susrawan, I Nyoman Adi; Budiningsih, Desak Nyoman; Laksmi, Ni Nyoman Ayu Tri; Karinda, Yuliana Olgadesti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Realizing the 2045 golden generation for the millennial generation, it is more relevant to do this with an educational trilogy such as family, school and community. Therefore education has an important role through intellectual intelligence education as well as human abilities can be developed so that education is believed to be the best solution. Various efforts have been made by the government to improve the quality of education in Indonesia through increasing teacher professionalism, such as through upgrading, training, and teacher certification. The aims of this study is to analyzing teaching behavior of public high school teachers after teacher certification. This research is a quantitative descriptive study with the number of respondents being 3 certified high school model teachers and 80 students involved in filling out the Teacher Behavior Inventory (TBI) questionnaire which includes aspects of clarity, enthusiasm, interaction, organization, speed, disclosure, speaking ability, and interpersonal relationships. The data obtained were analyzed using statistical analysis. The results of the study showed that the teaching behavior of public high school teachers after certification was in the good category.